Secondary spontaneous pneumothorax: a rare complication of pulmonary embolism. (29th October 2012) - Mathieson, Philip; Reckless, Ian; Ferrett, Colin
Abstract : An 85-year-old lady presented with a left middle cerebral artery territory infarct. Several days into her admission she became hypoxic and haemodynamically unstable. A CT pulmonary angiogram showed bilateral pulmonary emboli, right-sided parenchymal cavitation due to infarction and an associated large pneumothorax. She was treated successfully with an intercostal drain and anticoagulation. This case describes the rare phenomenon of secondary spontaneous pneumothorax due to pulmonary infarction from pulmonary embolism. The factors associated with the development of infarcts from pulmonary thromboemboli are poorly understood although a number of predisposing conditions and pathological features have been suggested. Pulmonary infarction occurs in around 10% of cases of pulmonary emboli but the complication of secondary spontaneous pneumothorax would appear to be much less common. One should consider pulmonary embolism as the cause of pneumothorax where there is significant clinical suspicion.